2001
DOI: 10.1046/j.1439-0450.2001.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Investigations on Reticuloendotheliosis in Turkey Flocks

Abstract: Four meat turkey and one turkey breeding flocks were surveyed for antibodies against reticuloendotheliosis virus (REV) at different intervals using commercial enzyme-linked immunosorbent assays. In addition, serum samples collected from 18 flocks at different ages were also tested for antibodies against REV. No antibodies were detected in any of the four meat turkey flocks that were surveyed. In the breeder flock, 20%) of tested samples from 1-day-old poults were positive. Between the fourth and 12th weeks all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…REV is the etiological agent of one of the most important immune-suppression diseases with a significant economic burden worldwide. Epidemiology investigation showed that REV is highly prevalent in poultry, but the etiology for it remains elusive (14)(15)(16)(17)(18). Recently, REV was verified that it can enter the semen and transmit by artificial insemination (19), which is consistent with the human immunodeficiency virus (HIV) (38) or Zika virus (ZIKV) (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…REV is the etiological agent of one of the most important immune-suppression diseases with a significant economic burden worldwide. Epidemiology investigation showed that REV is highly prevalent in poultry, but the etiology for it remains elusive (14)(15)(16)(17)(18). Recently, REV was verified that it can enter the semen and transmit by artificial insemination (19), which is consistent with the human immunodeficiency virus (HIV) (38) or Zika virus (ZIKV) (39).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, these integrated into the fowlpox virus (11,12) and gallid herpesvirus-2 (13) genomes, and then generated the recombinant DNA viruses that now circulate in wild birds and poultry. Although antibodies to REV are widespread in poultry (14)(15)(16)(17)(18), the etiology of REV infection remains elusive (8). Recently, a study confirmed that the REV can enter the semen and transmit by artificial insemination, but how the virus gets into semen was still unclear (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, it might be challenging to differentiate between distinct lymphoid tumor lesions caused by different viruses based on histological diagnosis. The use of an enzyme-linked immunosorbent assay (ELISA), which is more sensitive than indirect immunofluorescent-antibody testing and ap-propriate for veal flock screening, allowed for the successful detection of antibodies against REV (Smith and Witter 1983;Hafez 2001)…”
Section: Introductionmentioning
confidence: 99%